Nitrogen as a key regulator of flowering in Fagus crenata: understanding the physiological mechanism of masting by gene expression analysis. (7th August 2014) - Miyazaki, Yuko; Maruyama, Yosuke; Chiba, Yukako; Kobayashi, Masaki J.; Joseph, Benesh; Shimizu, Kentaro K.; Mochida, Keiichi; Hiura, Tsutom; Kon, Hirokazu; Satake, Akiko
Abstract: The role of resource availability in determining the incidence of masting has been widely studied, but how floral transition and initiation are regulated by the resource level is unclear. We tested the hypothesis that floral transition is stimulated by high resource availabiltiy in Fagus crenata based on a new technique, the expression analyses of flowering genes. We isolated F. crenata orthologues of FLOWERING LOCUS T, LEAFY and APETALA1, and confirmed their functions using transgenic Arabidopsis thaliana . We monitored the gene expression levels for 5 years and detected a cycle of on and off years, which was correlated with fluctuations of the shoot‐nitrogen concentration. Nitrogen fertilisation resulted in the significantly higher expression of flowering genes than the control, where all of the fertilised trees flowered, whereas the control did not. Our findings identified nitrogen as a key regulator of mast flowering, thereby providing new empirical evidence to support the resource budget model.